2005
DOI: 10.1007/s10643-005-0021-7
|View full text |Cite
|
Sign up to set email alerts
|

Municipal Intentions to Promote Preschool Children’s Capabilities and Health: A Descriptive Study of 25 Swedish Municipalities

Abstract: Preschools are environments where children are given opportunities to develop emotional, social and intellectual capabilities, characteristics that by recent research have been revealed as health protecting. The objectives of this study were to examine the intentions of 25 Swedish municipalities to develop such capabilities through activities in preschool and to relate these intentions to municipal socio-economic conditions. Indicators on municipal intentions to promote preschool children's emotional, social a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Regarding the influence of municipal demographic and socio-economic characteristics, similar results have been reported from previous studies. Guldbrandsson and Bremberg showed that growing municipalities reported fewer safety-promoting measures [ 46 ] and fewer measures aiming to promote mental health among preschool children [ 47 ] than municipalities with a stable population size. On the other hand, in these studies the proportion of the adult population with more than 12 years of education was not associated with the amount of health-promoting actions, i.e ., the intentions to promote young people's health appeared to be similar in municipalities with higher and lower percentage of well-educated people.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the influence of municipal demographic and socio-economic characteristics, similar results have been reported from previous studies. Guldbrandsson and Bremberg showed that growing municipalities reported fewer safety-promoting measures [ 46 ] and fewer measures aiming to promote mental health among preschool children [ 47 ] than municipalities with a stable population size. On the other hand, in these studies the proportion of the adult population with more than 12 years of education was not associated with the amount of health-promoting actions, i.e ., the intentions to promote young people's health appeared to be similar in municipalities with higher and lower percentage of well-educated people.…”
Section: Discussionmentioning
confidence: 99%
“…Three municipalities in Stockholm County in Sweden were invited to take part in the study. With the purpose of including municipalities with different emphases on child health promotion, the selection of municipalities was based on municipal child health promotion activity levels revealed in previous studies [14][15][16][17]. The three municipalities all agreed to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…The present study is the third phase of a research project. In the first phase, health-promoting activities directed toward children and adolescents in 25 Swedish municipalities were surveyed (described elsewhere) [14][15][16][17]. In the second phase, the development of child health-promoting activities in three Swedish municipalities was examined (described elsewhere) [13].…”
Section: Introductionmentioning
confidence: 99%